Analisis Fundamental Makro, Kebijakan Manajemen, Struktur Modal Kinerja Keuangan Terhadap Nilai Perusahaan dengan GCG Sebagai Moderasi pada Perusahaan Manufaktur Sektor Tekstil dan Garmen Yang Terdaftar di BEI - Missel, Rheinata Audreyna; Hwihanus (As-Syirkah: Islamic Economic & Financial Journal, 2024)
This study aims to evaluate the effect of macroeconomic fundamentals and management policies on company performance with capital structure and financial performance as intervening variables and the moderating role of Good Corporate Governance (GCG) in textile and garment sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2019-2023. The population in this study were all textile and garment sector manufacturing companies listed on the IDX. Data analysis techniques and hypothesis testing use statistical methods with a quantitative approach to test predetermined hypotheses. The results of this study indicate that macro fundamentals have a significant effect on financial performance and capital structure, but not on firm value. Management policy has a significant effect on financial performance and capital structure, but not on firm value. Financial performance has a significant effect on firm value, while capital structure has no significant effect. In addition, GCG does not moderate the effect of financial performance and capital structure on firm value. This study adds insight into the influence of macro fundamentals and management policies on firm value and the moderating role of GCG in the context of textile sector companies in Indonesia.